High-precision monitoring method for airport deformation based on time-series InSAR technology. (22nd February 2023) - Zhang, Rui; Zhang, Weiguang; Huang, Wei; Ma, Tao; Wang, Qing; Fang, Kexin; Wang, Kangnan
Highlights: Data denoising and precision assurance method is necessary to guarantee the InSAR measurement accuracy. The InSAR technology can accurately measure the vertical deformation within airport area. The InSAR collected data can be used to monitor if airport is stable using vertical deformation change rate. Abstract: In order to solve the problems of low efficiency and discrete data that are associated with current airport area deformation monitoring and to realize the long-term and large-scale deformation monitoring of ground objects at airports, this paper proposes a method to monitor deformation in airport using time-series interferometry synthetic aperture radar (InSAR) technology. Based on analysis of the technical principles and data processing methods of persistent scatterer (PS)-InSAR and small baseline subset (SBAS)-InSAR, 89 SAR datasets from two airports located in different areas that cover a three-year period were collected in this study. Using the collected data, data denoising and precision assurance methods, such as data cropping, connection graph generation, geocoding, etc., were researched. The deformation rate map and cumulative deformation variable map were analyzed to study the deformation development laws of the airport area for the different years. The three-year maximum settlement rate of the airport area investigated in this study is less than 70 mm/year, with the deformation rate concentrated between −13.34 mm/year and 14.54 mm/year. The sinking phenomenon is more significant than the uplift phenomenon in the Xianyang Airport area, indicating that the airport's foundation is relatively stable and concentrated. The settlement area is the junction of the southern cement runway and the D6 taxiway, and the settlement rate exceeds 30 mm/year.